The results of primary chemotherapy of TS-1/cisplatin regimen in unresectable or metastatic gastric cancer patients - Jung Hyun Song; Sang Woon Kim; Sun Kyo Song; Se Won Kim (Korean Journal of Clinical Oncology, 2014)
Purpose: This study was conducted to evaluate the response rate, side effect and resection rate after primary chemotherapy of TS-1/cisplatin regimen in unresectable or metastatic gastric cancer patients. Methods: From January 2005 to December 2012, 44 patients with unresectable or metastatic gastric cancer were enrolled onto the study. The regimen of primary chemotherapy was TS-1/cisplatin. Results: Unresectable or metastatic lesions were ascertained abdominal computed tomography (CT), positron emission tomography/CT and diagnostic laparoscopy. The factors of inoperability were 26 patients of peritoneal seeding, 8 tumor fixation, 7 mutiple liver metastasis, 15 multiple lymph node metastasis. They received TS-1/cisplatin regimen for primary chemotherapy. The response rates was 40.9% (18/44). The resection rate was 27.2% (12/44). Among 8 patients received curative resection and 4 received palliative resection. Median survival time were 41 months in cutative resection group, 21 months in palliative resection group and 8 months in non-resection group respectively (P=0.000). Conclusion: The response rates was 40.9% (18/44) and the resection rate was 27.2% (12/44). Resection group had longer survival than non-rescetion group. So aggressive treatment was needed to improve survival.